2018
DOI: 10.1177/0194599818793414
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Corticosteroids for Voice Outcomes among Patients Undergoing Thyroidectomy: A Systematic Review and Meta‐analysis

Abstract: Preoperative corticosteroids do not appear to reduce the risk of recurrent laryngeal nerve palsy following thyroid surgery. There is insufficient evidence to assess its effect on subjective voice outcomes. More robust randomized controlled trials are needed to assess the effectiveness of perioperative steroids in improving voice outcomes after thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…From this study, it was found that the effect of dexamethasone which significantly reduces the incidence of laryngeal edema. 11 In this study, the length of the operation performed did not significantly affect the final outcome of sound changes in the patient, and there were no complications such as PEAO in the patient, because the patient was relatively intubated for no more than 24 hours.…”
Section: Discussionmentioning
confidence: 57%
“…From this study, it was found that the effect of dexamethasone which significantly reduces the incidence of laryngeal edema. 11 In this study, the length of the operation performed did not significantly affect the final outcome of sound changes in the patient, and there were no complications such as PEAO in the patient, because the patient was relatively intubated for no more than 24 hours.…”
Section: Discussionmentioning
confidence: 57%
“…Although there was no consensus regarding their effect on postoperative voice quality, however, these studies showed that steroid administration effectively reduces pain, nausea, and vomiting after surgery. The recent meta-analyses concluded that there was insufficient evidence to claim perioperative systemic steroids' effect on improving voice outcomes after thyroid surgery [89][90][91]. The EBSLN, a branch of the vagus nerve, is the motor nerve to the cricothyroid muscle, an essential tensor of the vocal folds.…”
Section: Wang Et Al Analyzed the Benefits Of Intraoperative Corticosteroids For Reducing Rln Palsymentioning
confidence: 99%
“…Despite the inconsistent findings regarding the effects of steroid treatment on postoperative voice quality, those studies showed that steroid administration effectively reduces pain, nausea, and vomiting after surgery. Recent meta-analyses concluded that there was insufficient evidence to claim that perioperative systemic steroids effectively improve voice outcomes after thyroid surgery [ 89 - 91 ].…”
Section: Plan For Release and Update Of Guidelinesmentioning
confidence: 99%